Improving the Sustainable Infrastructure Development through Innovative Approaches in Technology, Management and Financial Aspects - Susantono, Bambang; Berawi, Abdur Rohim Boy (CSID Journal of Infrastructure Development, 2015)
Infrastructure covers various sectors that represent a large share of an economy and become a critical index of economic vitality. Both components of infrastructure: physical and social infrastructures are required to provide the necessary services for public interest. Reliable public utilities (e.g. power, telecommunication, water and gas supply, and other utilities), public works (e.g. roads, dams and canals, tunnels) and public transport (urban transport systems, railways, ports and waterways, and airports) are basic elements of a productive economy. Therefore, provision and maintenance of adequate infrastructure is essential for achieving rapid and sustainable economic growth. The adequacy of infrastructure helps to determine the country’s key success factors in increasing productivity, expanding trade and industry, coping with population growth, reducing poverty, improving environmental sustainability and living standards of the society. As massive investment is required, infrastructure development cannot be the responsibility of the public sector alone. Encouraging the participation of private sector investments is essential to maintain a sustainable infrastructure development. The public-private partnership will leverage a significant increase in additional finance, improve the project commercial viability and enhance the performance of the existing capital budget. Meanwhile, better management in the private sector can lead to an increased gain in project efficiency, leverage the capacity to innovate, as well as stimulate knowledge and technology transfer, which in turn will result in better quality and lower cost services.